MAIN APPROACHES TO THE DEFINITION OF ESSENCE OF A STATE POWER: EVOLUTION AND CURRENT STATE - Belyaeva, Galina; Belousova , Ksenia; Abgarov , Stepan; Kornev , Arkady; Zmerzly, Boris (Revista Inclusiones, 2019)
The paper discusses some issues regarding the essence and nature of state power. The main theories of power are analyzed, namely: coercive, Marxist, volitional, functional, conflictological, identification of power with the state (state mechanism or apparatus). We study the evolution of these approaches in accordance with the chronology of the emergence of relevant ideas and scientific concepts in conjunction with modern problems of determining state power.